The Role Of Intake Of Energy, Protein And Parenting With Nutrition Status Of Age 12 - 24 Months In Southern Meruya, West Jakarta - Indra Restu Kurniawan; Nanang Prayitno; Indah Kusumaningrum; Sugeng Wiyono; Meilinasari Meilinasari (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
Age 0-24 months is a period of rapid growth and development so often called the golden period as well as the critical period. The problem of growth disorders in infants and children under two years (baduta) needs to be addressed seriously. Therefore, every baby and child 12-24 months of age must get nutrition in accordance with their needs. The purpose of this study was to determine the role of energy intake, protein intake and parenting patterns with nutritional status of children aged 12-24 months in Meruya Selatan Village, West Jakarta. Cross Sectional research design. Population 400 toddlers. Sampling in this research using Stratified Random Sampling technique. The sample was 200 respondents. The study showed that the average energy intake of toddlers was 989.18 Calories. Most intake of fat is enough that is 69,5% (139 balita) while fat intake is included in less category that is 30,5% (61 under five). Most of the pattern of care in the good category that is 83% (166 children under five), while for not good category that is 17% (34 children under five). There was a relationship between energy intake (p = 0,000, r = -0.290), fat intake (p = 0.049; r = 0.139), parenting pattern (p = 0.036; r = -0.148) with nutritional status of children aged 12-24 months in Meruya Selatan Village, West Jakarta. There is a relationship between energy intake, fat intake and parenting pattern with nutritional status of children aged 12-24 months in Meruya Selatan Village, West Jakarta.